2021
DOI: 10.1111/1365-2664.13843
|View full text |Cite
|
Sign up to set email alerts
|

Wild and domestic savanna herbivores increase smaller vertebrate diversity, but less than additively

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Dung was not distinguished for four pairs of species: two zebra species (plains zebra Equus quagga and Grevy's zebra E. grevyi ) two hare species ( Lepus capensis and L. saxatilis ; Kartzinel et al., 2019), cattle/buffalo ( Bos indicus and Syncerus caffer ) and duiker/steenbok ( Sylvicapra grimmia and Raphicerus campestris ). A camera trapping study in KLEE (Wells, Kimuyu, et al., 2021) indicated that the number of independent detections (images separated by at least 1 hr) per trap night for plains zebra is 81 times that of Grevy's zebra for the treatments analysed in this study. The number of independent detections per trap night for duiker and buffalo were, on average, over three times that of steenbok and cattle respectively (Wells, Kimuyu, et al., 2021).…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…Dung was not distinguished for four pairs of species: two zebra species (plains zebra Equus quagga and Grevy's zebra E. grevyi ) two hare species ( Lepus capensis and L. saxatilis ; Kartzinel et al., 2019), cattle/buffalo ( Bos indicus and Syncerus caffer ) and duiker/steenbok ( Sylvicapra grimmia and Raphicerus campestris ). A camera trapping study in KLEE (Wells, Kimuyu, et al., 2021) indicated that the number of independent detections (images separated by at least 1 hr) per trap night for plains zebra is 81 times that of Grevy's zebra for the treatments analysed in this study. The number of independent detections per trap night for duiker and buffalo were, on average, over three times that of steenbok and cattle respectively (Wells, Kimuyu, et al., 2021).…”
Section: Methodsmentioning
confidence: 65%
“…A camera trapping study in KLEE (Wells, Kimuyu, et al., 2021) indicated that the number of independent detections (images separated by at least 1 hr) per trap night for plains zebra is 81 times that of Grevy's zebra for the treatments analysed in this study. The number of independent detections per trap night for duiker and buffalo were, on average, over three times that of steenbok and cattle respectively (Wells, Kimuyu, et al., 2021). For species pairs whose dung were not distinguishable, these differences in camera trap detections provide an indication of the contributions of each species to the combined dung of both species.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…However, whether this pattern persists at higher cattle stocking rates, or how the effects of high cattle stocking rates interact with the presence of native herbivore, is unknown. Investigating the effects of increasing cattle stocking rates is important because rangelands in this region, particularly those that are communally managed, are stocked at higher rates than the moderate stocking rates evaluated by Veblen et al (2016) (Crego et al, 2020; Wells, Kimuyu, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of cattle stocking rate and megaherbivores on cattle foraging efficiency were absent or weaker during the wet season (Figure 3). This may be because grass and forb availability is less limited, as evidenced by differences between treatments being smaller due to grazing-induced compensatory plant growth (McNaughton et al, 1983;Charles et al, 2017;Wells et al, 2021b). However, high cattle stocking rates and wild mesoherbivores suppressed cattle foraging efficiency more than additively in the wet season (Figure 3).…”
Section: Cattle Foraging Efficiency Responses To Cattle Stocking Ratementioning
confidence: 99%